Adverbian Phrase Structure in Karo Language - Soraya, Ratna; Mulyadi (East Asian Journal of Multidisciplinary Research, 2024)
In this research, adverbial phrases in the Karo language will be discussed. This research aims to find out, analyze and describe phrases in the Karo language. Data collection techniques were carried out using reading techniques and recording techniques or listening notes and analyzed using formal and informal qualitative descriptive analysis techniques. This research examines the structure of adverbial phrases in the Karo language, using qualitative research. Data were analyzed using distributional studies, there were 4 stages, namely data collection, data reduction, data presentation and conclusion of research findings and verification. The research results show that (1) there are three types of phrases found in the Karo language, namely: verb phrases (FV), adjective phrases (F Adj.) and adverb phrases (F. Ad).